Efficacy and Safety of Appropriate Shocks and Antitachycardia Pacing in Transvenous and Subcutaneous Implantable Defibrillators: Analysis of All Appropriate Therapy in the PRAETORIAN Trial. Issue 5 (14th November 2021) - Knops, Reinoud E.; van der Stuijt, Willeke; Delnoy, Peter Paul H.M.; Boersma, Lucas V.A.; Kuschyk, Juergen; El-Chami, Mikhael F.; Bonnemeier, Hendrik; Behr, Elijah R.; Brouwer, Tom F.; Kääb, Stefan; Mittal, Suneet; Quast, Anne-Floor B.E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The PRAETORIAN trial (A Prospective, Randomized Comparison of Subcutaneous and Transvenous Implantable Cardioverter Defibrillator Therapy) showed noninferiority of subcutaneous implantable cardioverter defibrillator (S-ICD) compared with transvenous implantable cardioverter defibrillator (TV-ICD) with regard to inappropriate shocks and complications. In contrast to TV-ICD, S-ICD cannot provide antitachycardia pacing for monomorphic ventricular tachycardia. This prespecified secondary analysis evaluates appropriate therapy and whether antitachycardia pacing reduces the number of appropriate shocks. Methods: The PRAETORIAN trial was an international, investigator-initiated randomized trial that included patients with an indication for implantable cardioverter defibrillator (ICD) therapy. Patients with previous ventricular tachycardia <170 bpm or refractory recurrent monomorphic ventricular tachycardia were excluded. In 39 centers, 849 patients were randomized to receive an S-ICD (n=426) or TV-ICD (n=423) and were followed for a median of 49.1 months. ICD programming was mandated by protocol. Appropriate ICD therapy was defined as therapy for ventricular arrhythmias. Arrhythmias were classified as discrete episodes and storm episodes (≥3 episodes within 24 hours). Analyses were performed in the modified intention-to-treat population. Results: In the S-ICD group, 86 of 426 patients received appropriate therapy, versus 78 of 423 patients in the TV-ICD group, during a median follow-up of 52 months (48-month Kaplan-Meier estimates 19.4% and 17.5%; P =0.45). In the S-ICD group, 83 patients received at least 1 shock, versus 57 patients in the TV-ICD group (48-month Kaplan-Meier estimates 19.2% and 11.5%; P =0.02). Patients in the S-ICD group had a total of 254 shocks, compared with 228 shocks in the TV-ICD group ( P =0.68). First shock efficacy was 93.8% in the S-ICD group and 91.6% in the TV-ICD group ( P =0.40). The first antitachycardia pacing attempt successfully terminated 46% of all monomorphic ventricular tachycardias, but accelerated the arrhythmia in 9.4%. Ten patients with S-ICD experienced 13 electrical storms, versus 18 patients with TV-ICD with 19 electrical storms. Patients with appropriate therapy had an almost 2-fold increased relative risk of electrical storms in the TV-ICD group compared with the S-ICD group ( P =0.05). Conclusions: In this trial, no difference was observed in shock efficacy of S-ICD compared with TV-ICD. Although patients in the S-ICD group were more likely to receive an ICD shock, the total number of appropriate shocks was not different between the 2 groups. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01296022.